Development of spray dried strawberry juice powder - Krishnan, Jagan Rao (2008)
This study explains the process and the optimum parameters to dry strawberry juice using laboratory scale spray dryer. The optimum parameters are the optimum drying temperature for minimum loss of vitamin C during drying process and optimum Maltodextrine 10 percentage for optimum colour, texture and taste of strawberry juice powder. There are 4 analytical experiments conducted on the strawberry juice powder produced which are vitamin C lost percentage, solubility analysis, effect of anti-caking and sensory evaluation. The strawberry juice is used as feed for spray drying process and production of strawberry powder. Firstly, strawberry juice is spray dried with spray dryer at various temperatures from 160 oC to 200 oC. Then, for the second experiment drying temperature is set constant at 170 oC and percentage of Maltodextrine is manipulated from 10% to 30%. Analytical experiment is conducted to measure the qualities of powder produced. Firstly, vitamin C loss studied before and after drying process to determine percentage of loss due to drying at different temperature. Then the solubility analysis conducted for powder produced with different percentage of Maltodextrine 10 addition. Then, the effect of anti-caking is analyzed by producing strawberry juice powder with addition of anti-caking agent (calcium carbonate). Lastly, sensory evaluation is conducted at cafeteria where people randomly choose to evaluate the qualities of reconstituted strawberry juice and powder produced. From the analysis, minimum loss of vitamin C observed at low temperature and it gradually increases as temperature increased. Solubility increases with increases of Maltodextrine 10 percentage. Anti-caking agent decreases hygroscopicity and increases the shelf life of powder. From all the analysis it is concluded that optimum temperature for drying is at 170 oC with optimum percentage of Maltodextrine 10 addition is 25%. High quality product is produced and it has high market potential in the future.